The decaying stuff of the Anthropocene: exploring contemporary trashscapes through ruination - Olli Pyyhtinen; Stylianos Zavos; Alma Onali; Ulla-Maija Sutinen; Niina Uusitalo (Digithum, 2023)
In this article, we take the notion of ruination beyond crumbling built structures and use it to explore contemporary trashscapes. With the waste produced by humanity scaling up to encompass the entire planet, we examine life with and in the ruins of the Anthropocene, where there is no Away to which the rejectamenta could be expelled and thus set apart from humans. On the one hand, we scrutinise waste as matter in a ruined state, subject to and resulting from a process of ruination; waste is a trace of an anterior presence that remains and continues to haunt us. On the other hand, we argue that collective wastage is turning the natural environment itself into ruins and landscapes into trashscapes. Towards the end of the article, we also stress the disruptive qualities of ruination and decay and discuss the renewed sensibilities evoked by waste. A life with waste in a world of Anthropocenic ruination amounts to a life that is not in complete control of itself but rather is inextricably entangled with otherness.